(untitled) (Journal of the Bangladesh Chemical Society, 2012)
Nanoparticles of silver and copper have been synthesized by reduction of aqueous silver nitrate and copper chloride solutions with sodium borohydride in anionic water-in-oil (w/o) microemulsions, sodium dodecyl sulphate (SDS)/1-pentanol/cyclohexane/water. Scanning electron microscopic (SEM) images, energy dispersive spectra (EDX) and UVspectra have been used to characterize the resultant nanoparticles. The average size of the nanoparticles has been found to be influenced by the water to surfactant molar ratio (Wo) in the microemulsions. Smaller particles are obtained at low Wo, while higher Wo yields larger particles. The antibiotic sensitivity of silver and copper nanoparticles against Escherichia coli (E. coli) was tested by zone inhibition method using nanoparticles in ethanol suspension. Both silver and copper nanoparticles showed the potential for use as antibacterial agents against E. coli with sensitivity as good as conventional antibiotics. Silver nanoparticles show higher antibacterial activity against E. coli, compared to copper nanoparticles. As the amount of the nanoparticles in the suspension decreases, antibacterial activity decreases; however the concentration dependence on antibacterial activity has been less pronounced. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11777 Journal of Bangladesh Chemical Society, Vol. 25(1), 71-79, 2012